Antikoagulan Parenteral Pada Intervensi Koroner Perkutan: Mekanisme Kerja, Monitoring, dan Faktor-Faktor yang Memengaruhi - Suprapta, Aloysius; Widito, Sasmojo (Jurnal Klinik dan Riset Kesehatan, 2025)
Background: The increasing number of heart attacks also followed by increases percutaneous coronary intervention (PCI). Coronary heart disease and PCI itself will increase the incidence of thrombosis in the coronary blood vessels. The use of parenteral anticoagulants and antiplatelets is necessary before, during and after PCI. Objective: Appropriate use of anticoagulants will provide expected benefits and avoid side effects such as bleeding. Accurate use of anticoagulants requires understanding the mechanism of action, monitoring drug consentration, and considering factors that influence the mechanism of action of anticoagulants. Discussion: There are three anticoagulants commonly used in Indonesia, namely unfractionated heparin, low molecular weight heparin (LMWH), and fondaparinux. These three anticoagulants affect the coagulation process by inhibiting thrombin formation. The profile of each anticoagulant has unique characteristics with heparin as an anticoagulant that is often used and easily available in health facilities, but has different reactions in each person, therefore requires regular monitoring. LMWH and fondaparinux have a more stable reaction so rarely require monitoring. Conclusion: Parenteral anticoagulants are useful in preventing the occurrence of thrombi before and during PCI procedures. Giving the right dose will reduce the effects of bleeding. Unfractionated heparin is an anticoagulant that often be used and available in health facilities but requires regular monitoring. Several factors can influence the mechanism of action of anticoagulants such as gender, body weight, kidney function, platelet count, smoking, and diabetes.